2015
DOI: 10.1002/jcsm.12008
|View full text |Cite
|
Sign up to set email alerts
|

Differences in food intake of tumour‐bearing cachectic mice are associated with hypothalamic serotonin signalling

Abstract: BackgroundAnorexia is a common symptom among cancer patients and contributes to malnutrition and strongly impinges on quality of life. Cancer-induced anorexia is thought to be caused by an inability of food intake-regulating systems in the hypothalamus to respond adequately to negative energy balance during tumour growth. Here, we show that this impaired response of food-intake control is likely to be mediated by altered serotonin signalling and by failure in post-transcriptional neuropeptide Y (NPY) regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 53 publications
(80 reference statements)
0
38
0
Order By: Relevance
“…The mouse allograft model of C26 adenocarcinoma is a well-established model for investigating body weight loss caused by cancer cachexia (16)(17)(18). We found that SARM-2f at doses of 10, 30, and 100 mg/kg increased the body (1.1-fold, 1.1-fold, and 1.1-fold, respectively), carcass (1.1-fold, 1.1-fold, and 1.1-fold, respectively), and levator ani muscle weights (3.3-fold, 2.9-fold, and 3.8-fold respectively) in the castrated mice (Fig.…”
Section: Prevention Of Body Weight Loss By Sa R M -2f Inmentioning
confidence: 99%
“…The mouse allograft model of C26 adenocarcinoma is a well-established model for investigating body weight loss caused by cancer cachexia (16)(17)(18). We found that SARM-2f at doses of 10, 30, and 100 mg/kg increased the body (1.1-fold, 1.1-fold, and 1.1-fold, respectively), carcass (1.1-fold, 1.1-fold, and 1.1-fold, respectively), and levator ani muscle weights (3.3-fold, 2.9-fold, and 3.8-fold respectively) in the castrated mice (Fig.…”
Section: Prevention Of Body Weight Loss By Sa R M -2f Inmentioning
confidence: 99%
“…Paradoxically, hypothalamic NPY gene expression is reported to be increased in animal models for chronic inflammatory diseases that are characterized by the presence of cachexia, such as cancer cachexia and arthritis [86][87][88][89][90][91]. However, this increase in mRNA levels did not correspond to the decrease in food intake [87,89,[91][92][93] (Fig. 1).…”
Section: Hypothalamic Inflammation: Orexigenic Signallingmentioning
confidence: 59%
“…Furthermore, these effects of serotonin on feeding and NPY levels are not apparently accomplished via affecting NPY gene expression [154,155]. Also in vitro, serotonin inhibits neuronal NPY secretion, while not affecting NPY gene expression [93]. Therefore, serotonin appears to play an active role in posttranscriptional failure of NPY in anorexia in chronic inflammation.…”
Section: Serotonin As Upstream Regulator Of Hypothalamic Resistancementioning
confidence: 96%
See 1 more Smart Citation
“…neuropeptide Y, melanocortin, corticotrophin‐releasing factor) converge on the nitric oxide/methylmalnyl coenzyme A system to modulate food intake 16, 37, 38, 39, 40. Serotonin is a particularly anorectic agent, and in cancer, the effect of serotonin is potentiated 41. Ghrelin produces its effects by stimulating nitric oxide synthase 42.…”
mentioning
confidence: 99%